Association between physical functions and quality of life in sarcoidosis - Marcellis, Rik; Lenssen, Antoine; Drent, Marjolein; De Vries, Jolanda (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: Quality of life (QOL) is often reduced in patients with sarcoidosis. Studies of the associations between physical functions and QOL are lacking. Objectives: So the aims of this study were (i) to evaluate the associations between QOL and physical functions, including muscle strength and exercise capacity, and other clinical characteristics, and (ii) to evaluate whether these associations change over a two-year period. Methods: Eighty-eight sarcoidosis patients (61 men; mean age: 46.1 ± 10.2 years) participated in a two-year follow-up to cross-sectional study. All patients completed the short World Health Organization Quality of Life assessment instrument (WHOQOL-BREF) and Fatigue Assessment Scale (FAS) at the baseline and follow-up assessments. Patients also performed a six-minute walk test (6MWT) and elbow flexor muscle strength, quadriceps and hamstrings peak torque tests. Maximal inspiratory pressure was recorded. Results: QOL in sarcoidosis remained stable over a two-year course of the disease, and was reduced compared with healthy controls, particularly regarding the physical health domain. Fatigue and the six-minute walking distance showed strong associations with QOL at both baseline and follow-up. Fatigue and exercise capacity predicted the scores for the WHOQOL-BREF physical health domain at baseline (59%) and follow-up (64%). QOL at baseline was the best predictor of QOL at follow-up. Conclusions: QOL is reduced in sarcoidosis. Fatigue and exercise capacity showed important stable associations with QOL, especially in the physical health domain. FAS and 6MWT should therefore be included in the management of sarcoidosis.